Large‐fragment insertion activates gene GaFZ (Ga08G0121) and is associated with the fuzz and trichome reduction in cotton (Gossypium arboreum). Issue 6 (7th February 2021) - Wang, Xiaoyang; Miao, Yuchen; Cai, Yingfan; Sun, Gaofei; Jia, Yinhua; Song, Song; Pan, Zhaoe; Zhang, Yuanming; Wang, Liyuan; Fu, Guoyong; Gao, Qiong; Ji, Gaoxiang; et al.
Summary: Cotton seeds are typically covered by lint and fuzz fibres. Natural 'fuzzless' mutants are an ideal model system for identifying genes that regulate cell initiation and elongation. Here, using a genome‐wide association study (GWAS), we identified a 6.2 kb insertion, larINDEL FZ, located at the end of chromosome 8, composed of a 5.0 kb repetitive sequence and a 1.2 kb fragment translocated from chromosome 12 in fuzzless Gossypium arboreum . The presence of larINDEL FZ was associated with a fuzzless seed and reduced trichome phenotypes in G. arboreum . This distant insertion was predicted to be an enhancer, located 18 kb upstream of the dominant‐repressor GaFZ ( Ga08G0121 ). Ectopic overexpression of GaFZ in Arabidopsis thaliana and G. hirsutum suggested that GaFZ negatively modulates fuzz and trichome development. Co‐expression and interaction analyses demonstrated that GaFZ might impact fuzz fibre/trichome development by repressing the expression of genes in the very‐long‐chain fatty acid elongation pathway. Thus, we identified a novel regulator of fibre/trichome development while providing insights into the importance of noncoding sequences in cotton.